Migraine Preventive Treatment Failure: A Cross-Sectional Study in a Tertiary Center in Brazil - Oliveira, Arão Belitardo (2023)
BackgroundIn Brazil, there is a scarcity of evidence on migraine burden in patients who have experienced previous preventive treatment failure (PPTF). ObjectiveTo evaluate the associations between ≥ 3 PPTF and clinical, psychiatric, and medical history data.MethodsIn a retrospective, cross-sectional study, the medical records of migraine patients who first visited a tertiary specialized clinic were examined. We selected adults of both sexes aged ≥ 18 who attended their first appointment between March and July 2017. Ordinal logistic regression models estimated the associations between number of PPTF (no previous treatment, 1 PPTF, 2, and ≥ 3 PPTF) and chronic migraine, the number of diagnosis exams performed, abortive drugs classes used, and non-pharmacological treatments tried (all categorized as none, 1- 3, and ≥ 4),  and severe depression (PHQ-9 ≥ 15) and anxiety (GAD-7 ≥ 15), adjusted for sex, age, and years with disease.ResultsData from 440 patients (72.1 % female) with a mean (SD) age of 37.3 (13.0) years were analyzed. The frequency of no previous treatment was 37.7 % (166/440), while 31.8 % (140/440) showed ≥ 3 PPTF. In patients with ≥ 3 PPTF, 35.7 % (50/140) had episodic, and 64.3 % (90/140) had chronic migraine. Compared to no previous treatment, patients with ≥ 3 PPTF showed higher odds (95 % confidence interval) for chronic migraine [2.10 (1.47, 2.98)], ≥ 4 diagnosis exams [6.59 (3.38, 12.84)], ≥ 4 abortive drug classes [16.03 (9.53, 26.94)], ≥ 4 non-pharmacological treatments [5.91 (3.07,11.35)], and severe depression [1.75 (1.07, 2.88)] and anxiety [1.73 (1.05, 2.85)]. ConclusionPatients first visiting a headache specialist had a high frequency of non-response treatment associated with higher migraine burden in terms of chronification, psychiatric comorbidity, acute medication and non-pharmacological treatment inefficacy, and unnecessary exams.